(untitled) (Fiep Bulletin - online, 2016)
In the universe of human activities, the body acts as the primary instrument of communication and sociability. In the dynamic display of multiple bodies, resulting bodily conceptions of cultural processes will establish relations approaches, distancing, acceptance, denial of identity values ??transmitted by corporeality. The purpose of this article is to discuss the issue of construction of beauty linked to ethnic and race relations, in order to understand how in modern society, arising under the logic of the colonization process, presents the search for an ideal of bodily beauty, marked by whiteness. This dimension, ethnocentric at its core, allocate the remaining bodies (not white), distant spread of the profile. So lovely body becomes synonymous with white body. In the spaces for the "cult of the body", namely, aesthetic clinics and academies, these dimensions are observable and is in this sense that the discussions around these issues are fundamental.